A Bear Ate My Pear - Kent Salisbury (India McClanahan Book, 1998)
Wacky pop-ups morph from one image to another in this fun and interactive skill-building book. Developed by education experts based on time-tested reading fundamentals A natural introduction to word recognition and basic reading skills - utilizing popular phonics fundamentals Full of fantastic interactive pop-ups that children love Look for other books
Keywords: PY Language -- PY Language